Strategi Komunikasi E-Commerce pada Gitar Listrik Ibanez di Bandung - Hadi Baku Pangestu (UPT Publikasi Ilmiah UNISBA, 2024)
This study aims to determine the marketing techniques used by Nada musical instrument store for Ibanez electric guitars through Instagram social media. These marketing techniques involve uploading product photos and testimonial photos to the Nada musical instrument store account. The product photos and testimonials to be uploaded to the Nada musical instrument store Instagram account are first discussed by the store owner and the Nada musical instrument store administrator. This discussion is to determine the quality of the uploads and the rules that apply on Instagram social media. This research is qualitative research with a case study approach. The sample for this research was taken using purposive sampling with a sample size of two key informants, namely the owner and administrator of the Nada musical instrument store's Instagram account, and additional informants from consumers who visited the store. The results show that the Nada musical instrument store uses testimonial and product photos to attract the attention of followers and netizens and also to demonstrate credibility to followers and netizens.